THE PREPARATION AND THERMAL-DECOMPOSITION OF SOME METAL-COMPOUNDS OF 4-DIMETHYLAMINOBENZYLIDENEPYRUVATE IN THE SOLID-STATE - Rasera, D. E.; Oliveira, LCS; Melios, C. B.; Ionashiro, Massao [UNESP] (Elsevier B.V., 1995)
Solid M-DMBP compounds, where M represents Mg(II), Ca(II), Sr(II), Ba(II), Ni(II), Cu(II), Zn(II), Fe(III), La(III), Th(IV), and DMBP is 4-dimethylaminobenzylidenepyruvate, have been prepared. Thermogravimetry-derivative thermogravimetry (TG-DTG), differential scanning calorimetry (DSC) and other methods of analysis have been used to characterize and to study the thermal stability and thermal decomposition of these compounds.
Keywords: DECOMPOSITION; DSC; DTG; STABILITY; TG; XRD